Preparation and characterization of a supported system of Ni2P/Ni12P5 nanoparticles and their use as the active phase in chemoselective hydrogenation of acetophenone - Costa, Dolly Carolina (2018)
Ni2P/Ni12P5 nanoparticles were obtained by thermal decomposition of nickel organometallic salt at low temperature. The use of different characterization techniques allowed us to determine that this process produced a mixture of two nickel phosphide phases: Ni2P and Ni12P5. These nickel phosphides nanoparticles, supported on mesoporous silica, showed activity and high selectivity for producing the hydrogenation of the acetophenone carbonyl group to obtain 1-phenylethanol. This is a first report that demonstrates the ability of supported Ni2P/Ni12P5 nanoparticles to produce the chemoselective hydrogenation of acetophenone. We attribute these special catalytic properties to the particular geometry of the Ni–P sites on the surface of the nanoparticles. This is an interesting result because the nickel phosphides have a wide composition range (from Ni3P to NiP3), with different crystallographic structures, therefore we think that different phases could be active and selective to hydrogenate many important molecules with more than one functional group.